An enhanced nylon material and its preparation method

By adding a specific proportion of PA66, glass fiber, silane coupling agent and reinforcement to the nylon material and processing it in a screw extruder, the problem of insufficient impact toughness of nylon material is solved, and the high strength and flame retardant performance is improved, which is suitable for the needs of plastic steel nail materials in the automotive field.

CN118406372BActive Publication Date: 2025-06-10RUIAN JUNCHENG PLASTIC MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410577487.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-06-10
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The existing nylon materials have shortcomings in impact toughness, which is difficult to meet the high strength and flame retardant needs of plastic steel nails in the automotive field.

Method used

By stirring and mixing PA66, glass fiber, silane coupling agent and specific reinforcement in a specific proportion, and heating and extruding in a screw extruder, a reinforced nylon material is formed to improve its tensile resistance and impact toughness.

Benefits of technology

The excellent tensile strength and impact toughness of nylon materials are achieved, so that the prepared plastic steel nails have good performance, and the partially selected reinforcement can also improve the flame retardant performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005338334130000031
    Figure GDA0005338334130000031
  • Figure GDA0005338334130000041
    Figure GDA0005338334130000041
  • Figure GDA0005338334130000051
    Figure GDA0005338334130000051
Patent Text Reader

Abstract

This application relates to plastic-steel nails and discloses a reinforced nylon material and a preparation method thereof. The reinforced nylon material includes the following raw materials in parts by mass: 50 parts of PA66; 25-40 parts of glass fiber; 0.4-1 part of silane coupling agent; 0.11-0.32 part of reinforcing agent; the reinforcing agent is one of monobutyl phosphate, dibutyl phosphate, tributyl phosphate, tricarboxylic acid, and ethane tricarboxylic acid. After adding a specific reinforcing agent, the reinforced nylon material of this application can have excellent toughness and tensile resistance, enabling the plastic-steel nails prepared therefrom to have good properties. Moreover, some of the selected reinforcing agents can further improve the flame retardancy of the reinforced nylon material, meeting the strength and flame retardancy application requirements of plastic-steel nails in the automotive field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to plastic-steel nails, and particularly to a reinforced nylon material and a preparation method thereof. Background Art

[0002] Plastic-steel nails are made of organic polymer materials and have nail-shaped parts. They are used in the automotive field to replace the original metal nails. On the one hand, they serve the purpose of weight reduction. On the other hand, whether during the installation process or after installation, no sparks will be generated when plastic-steel nails collide or rub against the metal frame, resulting in higher safety.

[0003] During the use of plastic-steel nails, the stress conditions of plastic-steel nails are different at different installation nodes. There is a tensile force along the nail body direction and a shear force perpendicular to the nail body direction. Moreover, with the switching of the movement and rest of the used product, the plastic-steel nails are affected by the movement impulse, and the tensile force and shear force they receive will be amplified. Therefore, the materials used for plastic-steel nails should have good tensile resistance and impact toughness. The existing nylon materials reinforced with glass fiber show excellent tensile strength but are insufficient in impact toughness. Therefore, this application hopes to develop a reinforced nylon material with both excellent tensile strength and excellent toughness to meet the material requirements of nylon plastic-steel nails. Summary of the Invention

[0004] To meet the material requirements of nylon plastic-steel nails, a reinforced nylon material and a preparation method thereof are provided.

[0005] The above first object of the present invention is achieved by the following technical solutions:

[0006] A reinforced nylon, comprising the following raw materials in parts by mass:

[0007] 50 parts of PA66;

[0008] 25 - 40 parts of glass fiber;

[0009] 0.4 - 1 part of silane coupling agent;

[0010] 0.29 - 0.48 part of reinforcing agent;

[0011] The reinforcing agent is one of monobutyl phosphate, dibutyl phosphate, tributyl phosphate, tricarboxylic acid, and ethane tricarboxylic acid.

[0012] By adopting the above technical solution, the compatibility of glass fiber with PA66 is enhanced under the action of silane coupling agent, and then it is dispersed and mixed into PA66, and there is no fiber floating on the surface, enhancing the impact fracture strength and tensile fracture strength of PA66. At the same time, the reinforcing agent and PA66 are reacted under the action of high temperature in the screw extruder to produce new amides, thereby crosslinking the original PA66 molecular chains, strengthening the organic polymer molecular chain network structure, and then enhancing the impact fracture strength and tensile fracture strength of nylon;

[0013] Therefore, the reinforced nylon material of the present application has excellent toughness and tensile resistance, making the plastic-steel nails prepared therefrom have good performance.

[0014] Optionally, the reinforcing agent is one of monobutyl phosphate, dibutyl phosphate, and tributyl phosphate.

[0015] By adopting the above technical solution, while the reinforcing agent improves the toughness and tensile resistance of the nylon material, it also improves the flame retardant performance of the nylon material.

[0016] Optionally, the reinforcing agent is dibutyl phosphate.

[0017] By adopting the above technical solution, the remaining hydroxyl groups have better activity under the action of the other two ester groups and are more likely to react with the amino group at a lower temperature. After the dibutyl phosphate is incorporated into the polymer chain, the reaction is carried out again after subsequent heating. Thus, the obtained crosslinked network is more uniform, and the toughness and strength of the obtained nylon material are better.

[0018] Optionally, it further includes 2.4 - 4.3 parts of maleic anhydride grafted PP.

[0019] By adopting the above technical solution, the maleic anhydride grafted on the maleic anhydride modified PP can react and combine with small molecules in the screw extruder, reducing pores and inhibiting the outward migration of additives. At the same time, the maleic anhydride grafted PP also has an effect of enhancing and toughening the nylon material.

[0020] Optionally, it further includes 5.1 - 7.3 parts of modified alumina powder.

[0021] The modified alumina powder is obtained by modifying the surface of alumina with amino siloxane.

[0022] By adopting the above technical solution, the alumina can be uniformly dispersed in the nylon material only after being modified with amino siloxane. Its porous surface can melt the raw materials and the migration of additives in the formed product. At the same time, it also has a certain effect of enhancing and toughening the nylon material.

[0023] Optionally, the amino siloxane is bis(trimethoxysilylpropyl)amine.

[0024] By adopting the above technical solution, the amino siloxane used for alumina modification is bis(tri-methoxysilylpropyl)amine, and the obtained reinforced nylon material has good performance.

[0025] The second object of the present invention is achieved by the following technical solution:

[0026] A method for preparing reinforced nylon, comprising the following steps:

[0027] Mix the raw materials except glass fiber, including silane coupling agent, PA66 resin, and reinforcing agent, evenly to obtain a mixture; pour the mixture into a screw extruder, and at the same time add glass fiber from the side feeding port of the screw extruder, and extrude and granulate or injection mold.

[0028] By adopting the above technical solution, the obtained nylon material has excellent tensile resistance and impact toughness.

[0029] In summary, the present application has at least the following beneficial effects:

[0030] After adding a specific reinforcing agent, the reinforced nylon material of the present application can have excellent toughness and tensile resistance, enabling the plastic-steel nails prepared therefrom to have good performance, and some of the selected reinforcing agents can further improve the flame retardancy of the reinforced nylon material, meeting the strength and flame retardancy application requirements of plastic-steel nails in the automotive field. Detailed implementation mode

[0031] Raw materials:

[0032] The materials not otherwise specified in this application are all commercially available products.

[0033] The parameters of some products are as follows:

[0034] PA66 is BASF PA66 A3HG2;

[0035] The glass fiber is an alkali-free glass fiber with a length of 1 cm and a diameter of 10 μm;

[0036] Maleic anhydride modified PP is DuPont Dow 50E739;

[0037] PP is Yanshan Petrochemical SP179.

[0038] Example 1

[0039] A reinforced nylon material, the raw materials of which are PA66, glass fiber, silane coupling agent, reinforcing agent, and flow agent.

[0040] The silane coupling agent is silane coupling agent KH570;

[0041] The reinforcing agent is monobutyl phosphate;

[0042] The mass ratio of the dosages of PA66, glass fiber, silane coupling agent, and reinforcing agent is 50:35:0.6:0.28.

[0043] The preparation method of the reinforced nylon material is as follows:

[0044] Weigh PA66, glass fiber, silane coupling agent, and reinforcing agent according to the mass ratio;

[0045] First, put the PA66 resin into an oven and bake it at 80 °C for 5 hours;

[0046] Then, stir and mix the silane coupling agent, reinforcing agent, and PA66 resin evenly to obtain a mixture;

[0047] Pour the mixture into a screw extruder, and at the same time add the glass fiber from the side material feeding port of the screw extruder. The parameters of the screw extruder are as follows,

[0048] Temperature: The first zone is 255 °C, the second zone is 255 °C, the third zone is 265 °C, the fourth zone is 255 °C, the fifth zone is 245 °C, the sixth zone is 235 °C, the seventh zone is 225 °C, the eighth zone is 200 °C, the ninth zone is 190 °C, and the head is 250 °C; The main machine speed is 500 rpm, the main feeding port speed of the mixture is 16 rpm, and the side material feeding port speed of the glass fiber is 12 rpm; The vacuum degree is 0.02 MPa;

[0049] Extrude to obtain the reinforced nylon material.

[0050] Examples 2 - 5

[0051] A reinforced nylon material, which is different from Example 1 in that the reinforcing agent is different, and the dosage is the optimal selection dosage ratio of each reinforcing agent, as shown in Table 1 below.

[0052] Table 1. Selection of reinforcing agent and mass ratio of each raw material dosage in Examples 1 - 5

[0053]

[0054]

[0055] Comparative Example 1

[0056] A reinforced nylon material, which is different from Example 1 in that no reinforcing agent is added to the raw materials, that is, its raw materials are PA66, glass fiber, and silane coupling agent, and the dosage ratio is that the mass ratio of the dosages of PA66, glass fiber, and silane coupling agent is 50:35:0.6.

[0057] Comparative Example 2

[0058] A reinforced nylon material, which is different from Example 3 in that trioctyl phosphate is used to replace tributyl phosphate in the raw materials, and the dosage ratio is that the mass ratio of the dosages of PA66, glass fiber, silane coupling agent, and trioctyl phosphate is 50:35:0.6:0.79.

[0059] Comparative Example 3

[0060] A reinforced nylon material, which is different from Example 3 in that triethyl phosphate is used to replace tributyl phosphate in the raw materials, and the dosage ratio is that the mass ratio of the dosages of PA66, glass fiber, silane coupling agent, and triethyl phosphate is 50:35:0.6:0.33.

[0061] The impact strength, tensile fracture strength, and fire rating of the reinforced nylon materials obtained in Examples 1 to 5 and Comparative Example 1 were tested to detect the toughness, strength, and flame retardancy of the reinforced nylon materials.

[0062] Impact strength: The 23°C cantilever beam notched impact test was carried out according to GB / T 1843-2008, and the specimen size was 80 mm × 10 mm × 4 mm;

[0063] Tensile strength: It was determined according to the test method of GB / T 1040.1-2006.

[0064] Fire rating: Tested according to the UL94 vertical burning method.

[0065] The test results are as follows.

[0066] Table 2. Test results of Examples 1 to 5 and Comparative Examples 1 to 3

[0067] <![CDATA[Impact strength (kJ / m 2 )]]> Tensile strength / (MPa) Flame retardant grade Example 1 26.1 144.3 V-0 Example 2 29.8 167.2 V-0 Example 3 25.5 140.8 V-0 Example 4 27.0 149.6 V-2 Example 5 27.8 154.9 V-2 Comparative example 1 19.8 105.6 V-2 Comparative example 2 22.1 119.7 V-1 Comparative example 3 17.6 104.2 V-2

[0068] Combined with Table 2, it was found by comparison that the impact strength and tensile strength of Examples 1 to 5 were better than those of Comparative Example 1, and among them, the flame retardant properties of Examples 1 to 3 were also significantly better than those of Comparative Example 1. Therefore, in this application, using one of monobutyl phosphate, dibutyl phosphate, tributyl phosphate, malonic acid, and ethanetricarboxylic acid as an enhancer can effectively enhance the strength and toughness of nylon materials, and when using one of monobutyl phosphate, dibutyl phosphate, and tributyl phosphate as an enhancer, the flame retardancy of nylon materials can be further improved.

[0069] Furthermore, comparing Examples 1 to 3 and Comparative Example 2, especially comparing Example 3 and Comparative Example 2, when the phosphoric acid alkyl ester is used as an enhancer, if the carbon chain length of the alcohol combined with the phosphoric acid carboxyl group is too long, the reaction activity will be slower, and the synergistic effect of the phosphoric acid alkyl ester on the strength and toughness of nylon will be significantly reduced.

[0070] Comparing Examples 1 to 3 with Comparative Example 3, especially comparing Example 3 with Comparative Example 3, when an alkyl phosphate is used as a reinforcing agent, if the carbon chain length of the alcohol bound to the phosphoric carboxyl group is too short, first, its boiling point is too low, and it is difficult to be used in the processing temperature during the production of nylon materials even when the pressurized environment inside the screw extruder fails. It is prone to boiling and decomposition, unable to play a reinforcing role, and the by-products after decomposition will also have an adverse impact on the toughness and strength of the nylon material.

[0071] Therefore, when an alkyl phosphate is selected as the reinforcing agent in this application, one of monobutyl phosphate, dibutyl phosphate, and tributyl phosphate is selected.

[0072] Further comparing Examples 1 to 3, it can be seen that the toughness and strength of Example 2 are better than those of Example 1 and Example 2. This is because the remaining hydroxyl groups in the dibutyl phosphate used in Example 2 have better activity under the action of the other two ester groups and are more likely to react with the amino group at a lower temperature. After the dibutyl phosphate is incorporated into the polymer chain, the reaction occurs again when the temperature is raised subsequently. As a result, the obtained crosslinked network is more uniform, and the toughness and strength of the obtained nylon material are better.

[0073] Examples 6 - 9

[0074] A reinforced nylon material, which is different from Example 2 in the amount of dibutyl phosphate used, specifically as follows:

[0075] Table 3. Mass ratio of raw material usage in Examples 6 - 9

[0076]

[0077] Examples 6 - 9 were tested, and the test results are shown in the following table.

[0078] Table 4. Test results of Examples 6 - 9

[0079]

[0080]

[0081] Combining Table 2 and Table 4, it can be seen that when dibutyl phosphate is used as the reinforcing agent in this application, the dosage ratio of the reinforcing agent to PA66 is preferably (0.23 - 0.42):50.

[0082] This application can also add common auxiliaries in the art such as lubricants and flow agents to adjust the formability of the nylon material during extrusion and the fluidity during melting.

[0083] Example 10

[0084] A reinforced nylon material, which further adds a lubricant and a flow agent on the basis of Example 1.

[0085] The lubricant is zinc stearate; the flow agent is erucamide.

[0086] The mass ratio of the raw material dosage is as follows:

[0087] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent = 50:35:0.6:0.28:0.15:0.13.

[0088] The preparation method is as follows:

[0089] Weigh the raw materials according to the mass ratio;

[0090] First, put the PA66 resin into an oven and bake it at 80 °C for 5 hours;

[0091] Then, stir and mix the silane coupling agent, reinforcing agent, PA66 resin, lubricant, and flow agent evenly to obtain a mixture;

[0092] Pour the mixture into a screw extruder, and at the same time add the glass fiber from the side material feeding port of the screw extruder. The parameters of the screw extruder are as follows,

[0093] Temperature: the first zone is 255 °C, the second zone is 255 °C, the third zone is 265 °C, the fourth zone is 255 °C, the fifth zone is 245 °C, the sixth zone is 235 °C, the seventh zone is 225 °C, the eighth zone is 200 °C, the ninth zone is 190 °C, and the head is 250 °C; the main machine speed is 500 rpm, the main feeding port speed of the mixture is 16 rpm, and the side material feeding port speed of the glass fiber is 12 rpm; the vacuum degree is 0.02 MPa;

[0094] Extrude to obtain the reinforced nylon material.

[0095] Example 11

[0096] A reinforced nylon material, which further contains a lubricant and a flow agent on the basis of Example 2.

[0097] The lubricant is zinc stearate; the flow agent is erucamide.

[0098] The mass ratio of the raw material dosage is as follows:

[0099] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent = 50:35:0.6:0.38:0.15:0.13.

[0100] The preparation method is as follows:

[0101] Weigh the raw materials according to the mass ratio;

[0102] First, put the PA66 resin into an oven and bake it at 80 °C for 5 hours;

[0103] Next, mix the silane coupling agent, reinforcing agent, PA66 resin, lubricant, and flow agent evenly to obtain a mixture.

[0104] Pour the mixture into a screw extruder, and at the same time add glass fiber from the side feeding port of the screw extruder. The parameters of the screw extruder are as follows.

[0105] Temperature: The first zone is 255 °C, the second zone is 255 °C, the third zone is 265 °C, the fourth zone is 255 °C, the fifth zone is 245 °C, the sixth zone is 235 °C, the seventh zone is 225 °C, the eighth zone is 200 °C, the ninth zone is 190 °C, and the die head is 250 °C; the main machine speed is 500 rpm, the main feeding port speed of the mixture is 16 rpm, and the side feeding port speed of the glass fiber is 12 rpm; the vacuum degree is 0.02 MPa.

[0106] Extrude to obtain a reinforced nylon material.

[0107] Example 12

[0108] A reinforced nylon material, which further contains a lubricant and a flow agent on the basis of Example 3.

[0109] The lubricant is zinc stearate; the flow agent is erucamide.

[0110] The mass ratio of the raw material dosage is as follows:

[0111] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent = 50:35:0.6:0.48:0.15:0.13.

[0112] The preparation method is as follows:

[0113] Weigh the raw materials according to the mass ratio.

[0114] First, put the PA66 resin into an oven and bake it at 80 °C for 5 hours.

[0115] Next, mix the silane coupling agent, reinforcing agent, PA66 resin, lubricant, and flow agent evenly to obtain a mixture.

[0116] Pour the mixture into a screw extruder, and at the same time add glass fiber from the side feeding port of the screw extruder. The parameters of the screw extruder are as follows.

[0117] Temperature: The first zone is 255 °C, the second zone is 255 °C, the third zone is 265 °C, the fourth zone is 255 °C, the fifth zone is 245 °C, the sixth zone is 235 °C, the seventh zone is 225 °C, the eighth zone is 200 °C, the ninth zone is 190 °C, and the die head is 250 °C; the main machine speed is 500 rpm, the main feeding port speed of the mixture is 16 rpm, and the side feeding port speed of the glass fiber is 12 rpm; the vacuum degree is 0.02 MPa.

[0118] Extrusion yields the reinforced nylon material.

[0119] Comparative Example 4

[0120] A reinforced nylon material, which is further added with a lubricant and a flow agent on the basis of Comparative Example 1.

[0121] The lubricant is zinc stearate; the flow agent is erucamide.

[0122] The mass ratio of the raw material dosage is as follows:

[0123] PA66: glass fiber: silane coupling agent: lubricant: flow agent = 50:35:0.6:0.15:0.13.

[0124] The preparation method is as follows:

[0125] Weigh the raw materials according to the mass ratio;

[0126] First, put the PA66 resin into an oven and bake it at 80 °C for 5 hours;

[0127] Then, stir and mix the silane coupling agent, PA66 resin, lubricant, and flow agent evenly to obtain a mixture;

[0128] Pour the mixture into a screw extruder, and at the same time add the glass fiber from the side feed port of the screw extruder. The parameters of the screw extruder are as follows:

[0129] Temperature: the first zone is 255 °C, the second zone is 255 °C, the third zone is 265 °C, the fourth zone is 255 °C, the fifth zone is 245 °C, the sixth zone is 235 °C, the seventh zone is 225 °C, the eighth zone is 200 °C, the ninth zone is 190 °C, and the head is 250 °C; the main machine speed is 500 rpm, the main feed port speed of the mixture is 16 rpm, and the side feed port speed of the glass fiber is 12 rpm; the vacuum degree is 0.02 MPa;

[0130] Extrusion yields the reinforced nylon material.

[0131] After obtaining the nylon materials of Examples 10 - 12 and Comparative Example 4, it was found during storage that after the storage time of the particles exceeded 2 months, the surface of the particles became sticky. Therefore, the new nylon materials of Examples 10 - 12 and Comparative Example 4 were subjected to an additive migration test.

[0132] Additive migration test: Weigh 5 g of plastic particles, soak them in 100 g of cyclohexane, filter after soaking for 360 h, concentrate the filtrate and detect the amount of additives in the filtrate, and calculate the additive migration percentage based on the amount of additives (reinforcing agent, lubricant, flow agent) contained in 5 g of plastic particles.

[0133] Table 5. Detection results of Examples 10 - 12 and Comparative Example 4

[0134] Percentage of additive migration / % Example 10 3.74 Example 11 4.24 Example 12 4.88 Comparative example 4 2.31

[0135] As can be seen from Table 5, after adding reinforcing agents, lubricants, and flow agents, the nylon material or the components prepared therefrom will exhibit migration of the additives as the storage time prolongs, causing the components to become sticky or undergo color change.

[0136] The additives in Examples 10 to 12 are affected by the number of ester groups on monobutyl phosphate, dibutyl phosphate, and tributyl phosphate. The more the number of ester groups, the more obvious the migration of the additives. The reason is that the butanol generated after the reaction of monobutyl phosphate, dibutyl phosphate, and tributyl phosphate with amino groups has a fast removal rate during the gasification and removal process in the screw extruder, which changes the distribution state of the additives in the nylon material and makes it more inclined to be distributed on the surface of the nylon material, thus making the migration of the additives more obvious.

[0137] In this regard, when there are additives in the nylon material, this application has made improvements, and the improvement schemes are as follows in multiple examples.

[0138] Example 13

[0139] A reinforced nylon material, which further adds maleic anhydride grafted PP on the basis of Example 10.

[0140] The mass ratio of the raw material usage is as follows:

[0141] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: maleic anhydride grafted PP = 50:35:0.6:0.38:0.15:0.13:2.4.

[0142] Maleic anhydride grafted PP and PA66 resin are mixed together into a mixture.

[0143] Example 14

[0144] A reinforced nylon material, which further adds maleic anhydride grafted PP on the basis of Example 11.

[0145] The mass ratio of the raw material usage is as follows:

[0146] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: maleic anhydride grafted PP = 50:35:0.6:0.38:0.15:0.13:3.8.

[0147] Maleic anhydride grafted PP and PA66 resin are mixed together into a mixture.

[0148] Example 15

[0149] A reinforced nylon material, which further adds maleic anhydride grafted PP on the basis of Example 12.

[0150] The mass ratio of the raw material usage is as follows:

[0151] PA66: Glass fiber: Silane coupling agent: Reinforcing agent: Lubricant: Flow agent: Maleic anhydride grafted PP = 50:35:0.6:0.38:0.15:0.13:4.3.

[0152] The maleic anhydride grafted PP and the PA66 resin are mixed together into a mixture.

[0153] Example 16

[0154] A reinforced nylon material, which further adds amino silicone modified alumina on the basis of Example 10.

[0155] The amino silicone modified alumina is obtained by soaking alumina with a size of 50 ± 2 nm in a 6.2 wt% solution of bis(trimethoxysilylpropyl)amine, filtering and drying after soaking for 7.2 h.

[0156] The mass ratio of the raw material usage is as follows:

[0157] PA66: Glass fiber: Silane coupling agent: Reinforcing agent: Lubricant: Flow agent: Amino silicone modified alumina = 50:35:0.6:0.38:0.15:0.13:5.1.

[0158] The amino silicone modified alumina and the PA66 resin are mixed together into a mixture.

[0159] Example 17

[0160] A reinforced nylon material, which further adds amino silicone modified alumina on the basis of Example 11.

[0161] The amino silicone modified alumina is obtained by soaking alumina with a size of 50 ± 2 nm in a 6.2 wt% solution of bis(trimethoxysilylpropyl)amine, filtering and drying after soaking for 7.2 h.

[0162] The mass ratio of the raw material usage is as follows:

[0163] PA66: Glass fiber: Silane coupling agent: Reinforcing agent: Lubricant: Flow agent: Amino silicone modified alumina = 50:35:0.6:0.38:0.15:0.13:6.6.

[0164] The amino silicone modified alumina and the PA66 resin are mixed together into a mixture.

[0165] Example 18

[0166] A reinforced nylon material, which further adds amino silicone modified alumina on the basis of Example 12.

[0167] The amino-siloxane modified alumina is obtained by soaking alumina with a size of 50±2 nm in a 6.2 wt% solution of bis(trimethoxysilylpropyl)amine for 7.2 h, followed by filtration and drying.

[0168] The mass ratios of the raw materials are as follows:

[0169] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: amino-siloxane modified alumina = 50:35:0.6:0.38:0.15:0.13:7.3.

[0170] The amino-siloxane modified alumina and PA66 resin are mixed together to form a mixture.

[0171] Comparative Example 5

[0172] A reinforced nylon material, which further adds PP on the basis of Example 11.

[0173] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: PP = 50:35:0.6:0.38:0.15:0.13:3.8.

[0174] The PP and PA66 resin are mixed together to form a mixture.

[0175] Comparative Example 6

[0176] A reinforced nylon material, which further adds siloxane modified alumina on the basis of Example 11.

[0177] The siloxane modified alumina is obtained by soaking alumina with a size of 50±2 nm in a 6.2 wt% solution of dimethyldimethoxysilane for 7.2 h, followed by filtration and drying.

[0178] The mass ratios of the raw materials are as follows:

[0179] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: siloxane modified alumina = 50:35:0.6:0.38:0.15:0.13:6.6.

[0180] The siloxane modified alumina and PA66 resin are mixed together to form a mixture.

[0181] Comparative Example 7

[0182] A reinforced nylon material, which further adds 3-aminopropylmethyldiethoxysilane on the basis of Example 11.

[0183] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: 3-aminopropylmethyldiethoxysilane = 50:35:0.6:0.38:0.15:0.13:0.33.

[0184] The toughness, strength, percentage of additive migration, and flame retardancy of Examples 10 to 18 and Comparative Examples 4 to 7 were tested, and the test results are shown in the following table.

[0185] Table 6. Test Results of Examples 10 to 18 and Comparative Examples 4 to 7

[0186]

[0187]

[0188] Combined with Table 6, by comparing Examples 13 to 18 and Examples 10 to 12, it can be seen that

[0189] Maleic anhydride-modified PP was added in Examples 13 to 15. The maleic acid grafted on the maleic anhydride-modified PP can undergo small molecule reactions and combine in the screw extruder, reducing pores and inhibiting the outward migration of additives. Therefore, the obtained nylon materials have a significantly lower percentage of additive migration than Examples 10 to 12 and Comparative Example 4. Adding maleic anhydride-modified PP in this application can effectively reduce the influence of monobutyl phosphate, dibutyl phosphate, and tributyl phosphate on additive migration, and can also reduce the original migration of other additives.

[0190] Amino-siloxane-modified alumina was added in Examples 16 to 18. The alumina can be evenly dispersed in the nylon material under the modification of amino-siloxane, and its porous surface can melt the raw materials and the migration of additives in the molded product. Therefore, the obtained nylon materials have a significantly lower percentage of additive migration than Examples 10 to 12 and Comparative Example 4. Adding maleic anhydride-modified PP in this application can effectively reduce the influence of monobutyl phosphate, dibutyl phosphate, and tributyl phosphate on additive migration, and can also reduce the original migration of other additives.

[0191] Combined with Examples 5 to 7, it can be seen that by comparing Examples 5 to 7, which were respectively added with PP, alumina modified with amino-free siloxane, and amino-siloxane on the basis of Example 11, there was no obvious decrease in the additive migration rate. Therefore, when maleic anhydride-modified PP or amino-siloxane-modified alumina reduces additive migration in this application, the maleic anhydride grafted on the maleic anhydride-modified PP, the alumina carrier in the amino-siloxane-modified alumina, and the siloxane containing amino used for modification are necessary for their effects.

[0192] Example 19

[0193] A reinforced nylon material, which is different from Example 17 in that the amino-siloxane used for modifying the amino-siloxane-modified alumina is 3-aminopropylmethyldiethoxysilane.

[0194] Example 20

[0195] A reinforced nylon material, which is different from that in Example 17 in that the amino siloxane used for the modification of amino siloxane modified alumina is 3-aminopropyltriethoxysilane.

[0196] Example 21

[0197] A reinforced nylon material, which is different from that in Example 17 in that the amino siloxane used for the modification of amino siloxane modified alumina is 3-aminopropylmethyldiethoxysilane, and the mass ratio of the raw material dosage is as follows:

[0198] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: amino siloxane modified alumina = 50:20:0.4:0.38:0.15:0.13:6.6.

[0199] Example 22

[0200] A reinforced nylon material, which is different from that in Example 11 in that the amino siloxane used for the modification of amino siloxane modified alumina is 3-aminopropylmethyldiethoxysilane, and the mass ratio of the raw material dosage is as follows:

[0201] PA66: glass fiber: silane coupling agent: reinforcing agent: lubricant: flow agent: amino siloxane modified alumina = 50:40:1:0.38:0.15:0.13:6.6.

[0202] Examples 19 to 21 were tested for toughness, strength, percentage of additive migration, and flame retardancy, and the test results are shown in the following table.

[0203] Table 7. Test results of Examples 19 to 20

[0204] <![CDATA[Impact strength (kj / m 2 )]]> Tensile strength / (MPa) Percentage of additive migration / % Flame retardant grade Example 19 31.0 174.2 2.16 V-0 Example 20 31.6 176.3 1.96 V-0 Example 21 30.9 171.1 1.90 V-0 Example 22 33.4 180.3 2.08 V-0

[0205] Combining Table 6 and Table 7, it can be seen that compared with Example 11, Examples 19 to 20 have significant improvements in additive migration, and have improvements in impact strength and tensile strength. Therefore, the amino siloxane used for the modification of amino siloxane modified alumina in this application can also be 3-aminopropylmethyldiethoxysilane and 3-aminopropyltriethoxysilane.

[0206] Further comparing Example 17 with Examples 19 to 20, it is found that it is better to use bis(trimethoxysilylpropyl)amine as the amino siloxane for the modification of amino siloxane modified alumina.

[0207] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. Those skilled in the art can make modifications to this embodiment without creative contributions after reading this specification, but as long as they are within the scope of protection required by the present invention, they are protected by the patent law.

Claims

1. A reinforced nylon material, characterized in that: Including the following raw materials by mass: PA66 50 parts; Glass fiber 25-40 parts; Silane coupling agent 0.4-1 part; Enhancer 0.29~0.48 parts; The enhancer is one of monobutyl phosphate, dibutyl phosphate, tributyl phosphate, tricarbamic acid, and triacetic acid; Maleic anhydride grafted PP 2.4~4.3 parts; 5.1-7.3 parts of modified alumina powder, wherein the modified alumina powder is obtained by modifying the surface of alumina with aminosiloxane.

2. A reinforced nylon material according to claim 1, characterized in that: The enhancer is one of monobutyl phosphate, dibutyl phosphate and tributyl phosphate.

3. A reinforced nylon material according to claim 1, characterized in that: The enhancer is dibutyl phosphate.

4. The reinforced nylon material according to claim 1, characterized in that: The aminosilicone is bis(trimethoxysilylpropyl)amine.

5. The method for preparing the reinforced nylon material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The raw materials except the glass fiber, including the silane coupling agent, the PA66 resin, the reinforcing agent, the maleic anhydride grafted PP, and the modified alumina powder are stirred and mixed uniformly to obtain a mixture; The mixed material is poured into the screw extruder, and the glass fiber is added from the side material feeding port of the screw extruder for extrusion granulation or injection molding.

Citation Information

Patent Citations

  • Long glassfiber reinforced nylon composite material and preparation method thereof

    CN103849141A

  • Antioxidant nylon material

    CN107353633A

  • Polymer compositions for flame retardancy and / or improved melt dripping properties

    CN109072083A